Mircha Eliade and the ideology of traditionality (Eurasian Journal of Religious Studies, 2024)
This article examines the idea of traditionalism and the main works of Mircea Eliade (1907-1986), who is a Romanian, French and American religious scholar and one of the founders of the religious studies field. The classic work “Shamanism: Archaic Methods of Ecstasy” (1951) was also analyzed, which received special attention among the scientist’s works. The main directions of scientific research are religious studies, analysis of the idea of traditionalism, which goes beyond the field of view of religions in the modern era of globalization. Based on the works of Eliade, the significance of materialist and rationalist positions, the phenomena of formalism and traditionalism in the era of technical development is clarified. Defining the traditionalist critical cultural movement developing in Europe, conducting a comparative analysis of current problems of society. Analysis of scientific findings taking into account the period and environment of writing scientific texts. The article also discusses how scholars in the humanities and social sciences responded to Eliade's book, how Eliade's view of shamanism inspired many spiritual seekers in the West in the 1960s and 1970s, and later, with the advent of postmodernism, examining criticism of his view of shamanism. Key words: Mircea Eliade, traditionalism, shamanism, archaism, ethnology.